PROTOTIPE ROBOT PENGANTAR DOKUMEN BEBASIS ARDUINO UNO DENGAN KENDALI ANDROID (STARTUP) - Rizaldy Khair; Nurliadi Nurliadi (LPPM Politeknik LP3I Medan, 2020)
Documents in general are important documents that must arrive at whom the documents are given. Currently, document delivery is still done by someone. With the development of automation technology in industry, robots are needed to help meet their needs quickly. With this, robotics technology was developed to help lighten the work of humans in the future. A document delivery robot is a robot created to help employees deliver documents. This robot can deliver documents automatically. Basically, this document manager robot uses the Line Follower concept, which is by following a predetermined path to the desired room, then the authors develop with the control of the android application (startup). Writing program code using Arduino IDE 1.8.9 and using Android as a robot controller. This robot uses 4 channel line tracker sensors, 2 DC motors and motor drivers as controllers, Arduino uno as the brain in this robot system. The results of this study produce a robot that can deliver documents to two goals by following the control of the user through the android application. The time taken to go to the first room is faster than the robot to go to the second room because of the difference in path length.